Cataloger mentoring a survey of catalogers' perception on mentoring for skills development in academic libraries / M. A. Bello and Y. Mansor - Bello, M. A.; Mansor, Y. (2011)
Library services in digital age have become user self-exploration while the geometrical growth in information resources continued to task bibliographic control especially catalogers whose task is not only to provide efficient, and effective bibliographic control but in addition timely access to all resources. However, the Cataloguers' skills, knowledge and strength continued to dwindle in past decades that have generated concern to the profession worldwide. Decline in education, unsatisfactory learning/training infrastructure and lowly attitude to cataloguing courses by educators and students alike in Nigeria further eroded skill development and proficiency. Consequently, the cataloguers are short of skills needed to perform their duties. This in turn may affect library services provision. This study therefore seeks to discern what cataloguers across university libraries in Nigeria perceived of mentoring for skill development and critical role of mentoring for proficient cataloguing skill. The study investigates 1. The state of mentoring in academic libraries of Nigerian Universities, 2. The perception of catalogers on mentoring for cataloging skill development. The research question is specifically directed, at 1. What is the state of mentoring in academic libraries of Nigerian universities? a) Do Nigerian university libraries have mentoring programs for catalogers? b) What types of mentoring programs is available and how adequate and effective is the programs? 2. What is the perception of catalogers on mentoring? 3. What is the perception of catalogers on mentoring for cataloging skill development? The study adopted descriptive survey method. With the use of questionnaire, fifty cataloguers were sampled from five Nigerian public university libraries in five of the six geopolitical zones of the country. The survey conducted in November/December, 2009 used a five-point likert-scale questionnaire for data collection. From the total sample size, only 35 responses representing 70 percent was found useable for analysis. Findings revealed that cataloger uses three types of mentoring programs Supervisory (81%), Situational (19%) and Group (13%) mentoring. Ninety-four (94%) percent of the respondents felt mentoring enhances their descriptive cataloguing skills and the confidence to used work tools. While another 97% felt mentoring could be use for succession plans and as stability factor in term of changes. The catalogers perceived mentoring as vital tool for skill development, considered it to have organizational benefits and agreed mentoring can be use to address the challenges of skill deficiency for improvement in the profession.